Taper Preparation Variability Compared to Current Taper Standards Using Computed Tomography - Richard Gergi; Joe Abou Rjeily; Nada Osta; Joseph Sader; Alfred Naaman (International Journal of Dentistry)
Introduction. The purpose of this study was to compare the taper variation in root canal preparations among Twisted Files and PathFiles-ProTaper .08 tapered rotary files to current standards. Methods. 60 root canals with severe angle of curvature (between 25∘ and 35∘) and short radius (𝑟<10 mm) were selected. The canals were divided randomly into two groups of 30 each. After preparation with Twisted Files and PathFiles-ProTaper to size 25 taper .08, the diameter was measured using computed tomography (CT) at 1, 3, and 16 mm. Canal taper preparation was calculated at the apical third and at the middle-cervical third. Results. Of the 2 file systems, both fell within the ±.05 taper variability. All preparations demonstrated variability when compared to the nominal taper .08. In the apical third, mean taper was significantly different between TF and PathFiles-ProTaper (𝑃 value < 0.0001; independent 𝑡-test). Mean Taper was significantly higher with PathFile-ProTaper. In the middle-cervical third, mean Taper was significantly higher with TF (𝑃 value = 0.015; independent 𝑡-test). Conclusion. Taper preparations of the investigated size 25 taper .08 were favorable but different from the nominal taper.